Exploring the Impulsive Buying Behavior on TikTok Live Platform - Chandra, Hanry Caesar; Tanil, Silviyani; Sarendra, Tania Citra; Gunadi, Willy (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2023)
Abstract. This study aimed to analyze the relationship between Influencer Credibility on the TikTok live platform, Customers' Hedonic Motives, and Online Impulsive Buying Behavior with the moderating effect of Sensory Shopping Experience. Using a self-selection sampling method, a questionnaire was used to gather the data from TikTok users who have experienced shopping impulsively in the TikTok live shopping event where an influencer becomes the host. Out of 297 questionnaires distributed, there were 263 completed responses that can be further analyzed. SEM-PLS was used to analyze the data from 263 samples and evaluate the hypotheses. The findings showed that Influencer credibility positively influences consumers' hedonic motives, which influence online impulsive buying behavior. On the other hand, the sensory shopping experience does not have a significant effect in moderating the relationship between hedonic motives and online impulsive buying behavior. Keywords: Influencer credibility, hedonic motives, online impulsive buying behavior, sensory shopping experience Abstrak. Penelitian ini bertujuan untuk menganalisis hubungan antara Kredibilitas Influencer pada platform TikTok Live, Motif Hedonik Pelanggan, Perilaku Pembelian Impulsif Online, dengan efek moderasi dari Pengalaman Belanja Sensorik. Metode sampling self-selection digunakan dalam penelitian ini, dengan menggunakan kuesioner untuk mengumpulkan data dari pengguna TikTok yang memiliki pengalaman berbelanja impulsif dalam TikTok live shopping di mana seorang influencer menjadi host. Dari 297 kuesioner yang didistribusikan, terdapat 263 tanggapan yang lengkap yang dapat dianalisis lebih lanjut. Analisis SEM-PLS digunakan untuk menganalisis data dari 263 sampel dan mengevaluasi hipotesis. Temuan menunjukkan bahwa Influencer Credibility secara positif mempengaruhi Motif Hedonik Pelanggan di mana motif tersebut mempengaruhi Perilaku Pembelian Impulsif Online. Namun, pengalaman belanja sensorik tidak memiliki pengaruh yang signifikan dalam memoderasi hubungan antara motif hedonik dan perilaku pembelian impulsif online. Kata kunci: Kreditibilitas influencer, motif hedonik, perilaku pembelian impulsif online, pengalaman belanja sensorik